Existence of periodic solution for a tumor growth model with vaccine interaction - Çelik, Canan; Tuncer, Nigar Özarslan (Topological Methods in Nonlinear Analysis, 2019)
This paper is devoted to the study of existence of positive periodic solutions of a tumor-immune competition model with vaccine interaction. By using the continuation theorem of coincidence degree theory developed by Gains and Mahwin, we establish the sufficient conditions for the existence of periodic solutions.